Multimodal cues in L2 lexical tone acquisition: current research and future directions - Farran, Bashar M.; Morett, Laura M. (Frontiers in Education, 2024)
This review discusses the effectiveness of visual and haptic cues for second language (L2) lexical tone acquisition, with a special focus on observation and production of hand gestures. It explains how these cues can facilitate initial acquisition of L2 lexical tones via multimodal depictions of pitch. In doing so, it provides recommendations for incorporation of multimodal cues into L2 lexical tone pedagogy.